Sosialisasi dan Pelatihan Pembuatan Pupuk Organik Padat di Kelompok Tani Hortikultura, Kelurahan Kawangu-Sumba Timur - Lusia Lewu; Junaedin Wadu; Uska Peku Jawang; Suryani K.K.L Kapoe; Yonce Melyanus Killa; Melycorianda H. Ndapamuri; Marten U. Nganji; Elsa Christin Saragih (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Horticultural commodities are an important component in the development of agriculture that continues to grow. In order to fulfill family nutrition, horticultural cultivation is one of the routine jobs of farmers in Kawangu Village, Pandawai District-East Sumba which is located in a coastal area with an altitude of 40 meters above sea level. The soil conditions that are more dominated by sand and rocks cause farmers in the location to experience obstacles in fulfilling organic fertilizers as an important input in the process of cultivating horticultural plants. This community service activity is expected to provide new knowledge about making solid organic fertilizers so that farmers can apply them to horticultural plants. Community service activities are carried out using the PRA (Participatory Rural Approach) method including observation, problem identification, counseling, making solid organic fertilizers, mentoring and evaluation. Through this activity, farmers have succeeded in making solid organic fertilizers using local materials available around the horticultural land and have been applied directly in the cultivation of horticultural plants. This community service has been successfully implemented independently by farmers by utilizing leaf litter and livestock manure around the horticultural land.